Identification of Innovation Needs for Fetal Well-Being Monitoring: A Phenomenological Research - Purwati, Yuni; Wahyuntari, Evi; Cahya Subrata, Arsyad; Anisa, Diah Nur (Poltekkes Kemenkes Surakarta, 2025)
Background: Counting fetal movements is a vital assessment to determine the well-being of the fetus that can be carried out independently by pregnant women. Pregnant women need to be provided with tools that are easy, practical, safe and economical so they can get accurate results. Objective: To develop a fetal movement counting tool that can be used independently by pregnant women. Methods: Qualitative phenomenological research, carried out 1 June-31 Juli 2024. Research using a focus group discussion approach on 8 participants, pregnant women's health workers at Bantul Regional Health Centers, Yogyakarta, Indonesia. Sample criteria: willing to be a participant, actively serving in the maternal health unit, working at a Community Health Center with the highest Infant Mortality Rate. The sample was selected using purposive sampling, analysis techniques using compression, presentation and drawing conclusions NVivo 12 Pro International software. Results: A total of 246 codes were generated, 7 categories, 4 themes, namely: (1) previous behavioral experience; (2) perception of the benefits of calculating fetal movements; (3) experience of techniques for calculating fetal movements; and (4) expectations of the tools needed. There was main topic is need for monitoring fetal movementsaya Conclusion: The themes obtained are the basis for formulating a design to develop a fetal movement monitoring tool that can be carried out independently by pregnant women. The themes obtained imply that health workers need to encourage the use of simple and easy-to-operate foetal movement monitors that can be used independently to improve pregnancy monitoring based on maternal empowerment.